Social influences on student perceptions of failure in learning design processes: instructional implications. (3rd July 2017) - Tan, Michael; Lee, Shu-Shing; Ng, Zhi Ying
ABSTRACT: While the Silicon Valley aphorism would encourage all involved in design to 'fail early so that one can succeed earlier', such a concept may be hard to translate to classroom instructional strategies, especially due to the negative connotations of failure in school settings. Failures in design serve a somewhat distinct purpose from failures in schooling; however, for learners, this distinction is hard to distinguish, and the subjective experiencing of these forms can be highly similar. In this paper, we discuss the role of failure in learning, especially in the design process. We examine the ethnographic case study of a grade nine class involved in a design instruction course, and find that while students were aware of the positive attributes of failure, they had difficulty embracing failure as a classroom activity, and take risks to accomplish projects. We trace these perceptions to the social messaging around failure that these students experience, and discuss some implications these findings may have for failure, risk aversion, and ultimately, schools as sites for educating innovativeness in societies.